التعليم الرقمي وعلاقته بقلق المستقبل للطلبة الجامعيين في ظل أزمة كوفيد-19 - Nattah , Kamel; Aroussi , Derradji; Seghiri , Rabah (sports creativity, 2025)
Our study aims to investigate the positive and negative characteristics of digital education on the one hand, and the relationship of those aspects with university students' concerns about their professional and social future, and to know the effectiveness of digital education as an alternative to urban education COVID-19 crisis, and to confirm the hypotheses of our study we've chosen randomly a sample of 180 students from Mohammed Boudiaf University in M'sila during the 2019/2020 academic season, As for the approach used in the study, it is the descriptive one that depends on data collection, and we used the measure of future anxiety designed by Doaa Shalhoub in 2016, The study concluded with a number of results, the most important of which are Confirming the hypothesis of a correlation between digital education and future anxiety for students in light of the Corona crisis, as these programs played a positive role in reducing future anxiety